Examining the impact of both legal and nonlegal factors on following a vehicle too closely utilizing three deterrence-based theories. Issue 1 (March 2022) - Ochenasek, Michelle; Truelove, Verity; Stefanidis, Kayla B.; Watson-Brown, Natalie
Following a vehicle too closely (otherwise known as tailgating) is a high-risk behavior and major contributor to motor-vehicle collisions and injuries. Both legal and nonlegal countermeasures are currently in place in an attempt to prevent this behavior, yet there has been limited research that has examined the effectiveness of both legal and nonlegal factors on engagement in the behavior. Therefore, this research utilized a combination of the three most salient deterrence-based theories used in road safety to understand the impact of both legal and nonlegal sanctions on following a vehicle too closely. A survey was completed by 887 Queensland drivers aged 17–84 years ( M age   =  49 years; 55% males). Variables from Classical Deterrence Theory, the reconceptualized deterrence theory and the extended deterrence-based model (that includes perceived internal loss, physical loss, and social sanctions), as well as measures of following a vehicle too closely were used. The majority of the sample (98%) reported following a vehicle too closely at some point, with the average frequency ranging from rarely to sometimes. Significant predictors of more frequent unsafe following distances included: being male, younger in age, and avoiding punishment for the behavior. Meanwhile, significant predictors of less frequent unsafe following distances included knowing others who have been punished for the behavior, as well as fearing the physical and internal losses resulting from unsafe following distances. Notably, the severity of the punishment was also a significant deterrent, while the perceived certainty of being apprehended for the offence was low and did not impact engagement in behavior. These results have a number of important implications on how to maximize both legal and nonlegal countermeasures to further prevent following a vehicle too closely.